Knowledge as determinant in deciding expectant mother’s birth assistance at Taliwang Public Health Centre, West Nusa Tenggara, 2013 - M. Karjono; Luh Putu Lila Wulandari; Nyoman Tigeh Suryadhi (Universitas Udayana, 2013)
Regional government directives push for 90% of all expectant mothers to utilise birthing assistance from trained health care providers, however recent data from Taliwang Public Health Center indicates this falls well below the target only 56.8%. The choice of alternative forms of birthing assistance can often result in risky and dangerous birthing methods, thereby increasing the possibility of infant/maternal mortality. In order to explore this, a study to explore factors influencing the birth assistance choice at Taliwang Public Health Center was conducted. A cross sectional design was adopted in the study. Total sample of 160 pregnant mothers was selected from a total of 1068 population using systematic random sampling. Each respondent was interviewed using a questionnaire. Data were analysed using univariate, bivariate (chi square) and multivariate analysis (logistic regression). The results of bivariate analysis indicate that factors influencing a choice of birth assistance were: knowledge levels [X2=20.79; p=0.003]; access to the health service [X2=10.34; p=0.006], access to reliable information [X2=6.15; p=0.011), parent’s role [X2=10.64; p=0.002] and influence of authority/religious figures [X2=10.21; p=0.006). The multivariate analysis revealed that knowledge levels of mothers was the most significant and influential factor in birthing assistance choice [OR=2.02; p=0.013; 95%CI 1.16-3.51; R2=0.13]. It is evident that there is a need to upscale efforts in improving the knowledge levels of expectant mothers regarding risky birthing practices, through health promotion programs, and to increase the frequency of the current antenatal classes. Furthermore, studies regarding other factors which might influence expectant mothers birthing assistance choice, such as socio-cultural factors, the role of healthcare providers, traditional birthing mythologies could be explored.